(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
The article analyses the notion of «financial stability» in the context of sustainable development of the economy as a whole and the economic entity in particular. The classification of external and internal factors that affect the stability of an economic entity is proposed.